2017
DOI: 10.1016/j.conbuildmat.2017.04.160
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanical response of Hybrid Fiber Reinforced Concrete with Recycled and Industrial Steel Fibers

Abstract: This paper summarizes the results of an experimental research on “sustainable” cementitious composites internally reinforced with industrial and recycled steel fibers, the latter being recovered from waste tires and employed in substitution and/or addition of the industrial steel ones. Specifically, six concrete mixtures including different amount of industrial/recycled steel fibers were produced and tested both in compression and bending. The obtained results confirm the promising prospects already observed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
76
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 151 publications
(102 citation statements)
references
References 41 publications
6
76
0
2
Order By: Relevance
“…It's worth to highlight that samples indicated as reference samples are related to those which were not exposed to acid attack The compressive strength test showed that samples suffered the most damage by sulfuric acid, whereas the nitric acid samples with no fibers and with 100% metal fibers had increased strength values as compared with the reference mixtures. Caggiano et al (2017) [39] found out that the use of microfibers slightly influences the compressive strength of composites, opposing to the results obtained and showed at The results showed that the damage caused to conventional concrete were very similar for the three acids. Also, sulfuric acid was the acid that showed the greatest potential for concrete degradation.…”
Section: Resultsmentioning
confidence: 88%
“…It's worth to highlight that samples indicated as reference samples are related to those which were not exposed to acid attack The compressive strength test showed that samples suffered the most damage by sulfuric acid, whereas the nitric acid samples with no fibers and with 100% metal fibers had increased strength values as compared with the reference mixtures. Caggiano et al (2017) [39] found out that the use of microfibers slightly influences the compressive strength of composites, opposing to the results obtained and showed at The results showed that the damage caused to conventional concrete were very similar for the three acids. Also, sulfuric acid was the acid that showed the greatest potential for concrete degradation.…”
Section: Resultsmentioning
confidence: 88%
“…It can be observed from the previous experimental studies of steel and metallic fibers [7][8][9][10][11][12][13][14], natural fibers [15] and polymetric fibers [16][17][18] that the incorporation of single type of fibers in concrete does not significantly influence the various characteristics of concrete except strain and crack resistance, while the incorporation of hybrid fibers effectively increase the resistance to cracking and strain efficiency in several levels [19,20]. To improve the ductility, bridge the cracks and prevent their propagation in the concrete, the addition of fibers is an effective way [21].…”
Section: Introductionmentioning
confidence: 91%
“…Más específicamente, se partió de una mezcla de FRC de referencia con 0,5 % en volumen de fibras de acero industriales (industrial steel fibers, ISF), es decir 40 kg/ m 3 , y se prepararon tres mezclas más reemplazando el 25 %, 50 % y 100 % de dichas fibras con una cantidad igual de fibras recicladas (recycled steel fibers, RSF). De este modo, el comportamiento mecánico del hormigón reforzado solo con ISF fue comparado con el hormigón con un híbrido de fibras de acero (industriales y recicladas) y también con el hormigón reforzado solo con RSF, con el objetivo de determinar la factibilidad de su uso como material estructural Caggiano et al, 2017;. Las fibras de acero recicladas empleadas en este estudio (figura 2a) fueron suministradas por una empresa dedicada a recolectar y reciclar neumáticos usados.…”
Section: Incorporación De Fibras De Acero Recicladas En El Hormigónunclassified